Southern farmers and their stories : memory and meaning in oral history - Walker, Melissa, 1962- (New directions in southern history., 2006)
Examining oral history narratives of more than five hundred farmers from all the southern states, Melissa Walker explores how farmers recall their agrarian past and the lessons that they draw from that past. These farmers understood that their way of life was passing--indeed many of them would be pushed off the land forever--and so they told stories to preserve a sense that their way of life mattered. Landowners and sharecroppers; native-born farmers and immigrants, African Americans and whites; and men and women narrate the compelling story of how the rural South was modernized in the twentie.